EKSPLORASI MANAJEMEN LABA: PENGUJIAN FINANCIAL DISTRESS, KEPEMILIKAN INSTITUSIONAL, DIVIDEN, DAN MODERASI KOMISARIS INDEPENDEN - Putu Diajeng Intan Mayuni; Partiwi Dwi Astuti; Ida Ayu Surasmi (Jurnal Riset Akuntansi Warmadewa, 2025)
This study aims to examine the effect of financial distress, institutional ownership, dividends, and the role of independent commissioners in moderating earnings management in banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023. The research sample was obtained through a purposive sampling stage, which resulted in 18 companies with a total of 54 financial reports. Data analysis was carried out through the application of moderated regression analysis (MRA) through the use of the EViews 13 statistical program. The findings of this study describe in an empirical context, financial distress has a positive but insignificant effect on earnings management, institutional ownership has a negative and significant effect, while dividends have a positive and significant effect on earnings management. On the other hand, independent commissioners failed to moderate the effect of financial distress and dividends on earnings management, but were able to strengthen the effect of institutional ownership on earnings management..